Identifikasi Muatan Differential Item Functioning Pada Data Ujian Nasional Matematika - Samritin Samritin (Journal on Education, 2022)
One of the test criteria used in ability testing is a test that is free from Differential Item Functioning (DIF). Tests containing DIF can harm certain groups and benefit certain groups as well. However, sometimes the standard tests used are unknowingly containing DIF. The National Examination must meet the DIF-free criteria to avoid erroneous decision-making regarding the results of the exam. The purpose of this study is to detect Differential Item Functioning (DIF) through a unidimensional-based item response theory approach using explorative quantitative research. The results of the national mathematics exam as data for detecting DIF. The analysis technique uses the Mantel-Haenszal and Logistic Regression. In addition, DIF detection focused on gender, namely groups of men and women. Estimation of item parameters was carried out with the help of BILOG-MG, and the identification of DIF content using the R program tool. The results of the analysis showed that of the 21 items analyzed using Mantel-Haenszal and Logistic Regression, one item (Number 27) was suspected to contain DIF. This item is likely or suspected to benefit the male group, because in completing it the students first illustrate it in the form of an image, making it easier to calculate the height of the building, so that a long enough analysis is needed to be able to answer it.